A retrospective cohort study on the bidirectional association between depression and chronic kidney disease - Jeun, Ki Jin; Brothers, Todd; Shawwa, Khaled; Al-Mamun, Mohammad A. (Frontiers in Nephrology, 2026)
Rationale and objectivesDepression has been associated with worse clinical outcomes in individuals with chronic kidney disease (CKD), yet its influence on kidney disease progression in earlier CKD stages remains underexplored. Thus, this study investigates the role of depression on CKD progression by stages, and bidirectional relationship using real-world data.MethodsThis was a retrospective cohort analysis. Data was extracted from the TriNetX EMR database from 2007 to 2022. Patients (>18 years of age) with diagnosis of CKD were selected for the study. Key independent variables were diagnosis of depression or anxiety, identified by ICD codes, for the primary objective, and CKD stages (i.e., >3, 4, and 5) defined by KDIGO for the secondary objective. Primary outcome was progression to kidney disease (eGFR < 60 ml/min/bsa and > 40% decline in eGFR from the initial screening), and the secondary outcome was diagnosis of depression. Kaplan-Meier analysis and Cox proportional hazards model were used to evaluate the relationship between the dependent and independent variables while adjusting for covariates (sex, race, ethnicity, and age).ResultsDepression was significantly associated with a higher risk of kidney disease progression (HR = 1.94 [1.77–2.11], p<0.001). Among patients with CKD, patients with CKD stages 4 and 5 had significantly higher risks (HR = 1.26 [1.17–1.35] and 1.38 [1.23–1.54], p<0.001) of new diagnosis of depression than those in stage ≤3, respectively. These associations remained statistically significant after matching and adjusting for age, sex, race, and comorbidities.ConclusionDepression significantly accelerates CKD progression and patients with stage 5 CKD had the highest risk of developing depression. Our study advocates for integrating frequent mental health screenings for patients with CKD. This could improve patient outcomes and minimize negative consequences associated with depression.